Aculturación comunitaria y productiva en el territorio Cofán, parroquia Dureno, Provincia de Sucumbíos - Jumbo Procel, Adriana del Cisne (2015)
This research was conducted in the Cofán community Dureno Parish, which belongs to Canton Lago Agrio, Sucumbios Province, with the support of the authorities of the Indigenous Federation of the Cofan of Ecuador (FEINCE); same that lasted eight (8) months, in which tools will be applied as the holographic theory of human organization (TOH) and interviews that allowed to obtain the information necessary to comply with the objectives. As results was possible to determine the ancestral knowledge communication, the change in the productive, commercial, social and cultural practices; the youth population lives Cofan new generational wave that settlers and oil companies have implemented. According to the analysis highlights the impact on the cultural change in the Cofan community, mainly in the production and commercial areas, as currently raising cattle and pigs for marketing is identified due to the invasion of oil and settlers. In addition to frequent oil spills that have existed in their community have caused rivers are contaminated, fishing activity is decreased, the animals for hunting migrating to other sectors. It is recommended that workshops for upgrading and strengthening intergenerational communication of ancestral and spiritual codes with the youth of the community. Also strengthen communication of the benefits of medicinal plants by the Cofan elders and shamans.